Introduction to special section on clients’ perspective of change in psychotherapy - Roussos, Andres Jorge (2013)
The articles included in this special section are based on the works presented in a panel named Clients Talking About Therapy, which took place during the 43rd International Annual Meeting of the Society for Psychotherapy Research in Virginia Beach. One of the main issues at the time of the panel was the difficulty in reaching an agreement about what change represents in psychotherapy research. In this introduction I very briefly present some of the debates that are currently going on about change and the role of qualitative research in that debate. The articles included are qualitative investigations that study the value of clients’ perspectives from different vantage points. The authors used in-depth interviews, which allow interviewees to communicate whatever they think, enabling the emergence of new perspectives. I look forward to the application of the information obtained among these studies, in the development of applied clinical knowledge.